KAJIAN PERMASALAHAN LALU LINTAS PADA JALAN NASIONAL KABUPATEN SEMARANG BERBASIS SISTEM INFORMASI GEOGRAFIS (Geo-Image, 2016)
National road in Semarang regency have traffic load is very high with the problems of Traffic jam and traffic accidents. The purpose of this research are: 1) Identify the characteristics of the location of critical points of congestion and traffic accident-prone areas. 2) Make the handling of traffic jams. 3) Make the handling of a traffic accident in accident-prone areas. The method used in this study using quantitative research analysis technique level of service (LOS) and for crash analysis technique Z-Score as well as the ranking of the crash site to identify accident-prone areas. The research result is a level of service across the national road into the sample Semarang regency, during peak hour have class LoS D until class LoS E, and the average LoS C during the hours roll. Roads that identified accident-prone areas include roads Ungaran-Bawen with the number of the accidents amounted to 314 events with a Z-score of 1.80 and the accident rate 34.20 (100JPKP), roads Bawen-Salatiga with the accidents amounted to 142 events with the value of Z-score of 0.02 and the accident rate 35.47 (100JPKP) and roads Bawen-Temanggung with the accidents amounted to 176 events with a Z-score of 0.37 and the accident rate 21.35 (100JPKP).